Comparative Analysis of Mobile Learning Trends of Physical Education Teaching Students: Republic of Kosovo and Russia Example - Shemsedin Vehapi (Kassel University Press, 2021)
The aim of this research is to conduct a comparative analysis of the mobile learning trends of students of the physical education teaching department studying in The Republic of Kosovo and Russia. In this research, causal comparative research method was used. The study group consists of 40 students studying physical education teaching at various universities in Kosovo and Russia in the 2020-2021 academic year. A total of 80 students participated in the study. The research data were collected by the semi-structured interview form developed by the researcher and the data was analyzed by content analysis method. The research results reveal that students studying in both countries have a high mobile learning tendency. In addition, students from both countries have similarly defined the advantages and disadvantages of mobile device use in education.